Designing a balanced scorecard using a scenario approach. Issue 2 (3rd June 2019) - González, Miguel Angel; Quezada, Luis; Palominos, Pedro
Abstract : Purpose: The purpose of this paper is to design a method or process that relates dynamic environmental conditions with the strategic objectives present in a company's strategy map, thereby allowing rapid analysis and the generation of new strategies that the company can adopt in a timely manner in order to maintain and/or improve its competitive position in the market. Design/methodology/approach: One training session and three workshops were run involving the company staff. The intervention team reviewed and analyzed the results achieved and prepared the final presentation. Finally, they were asked to evaluate the intervention methodology with respect to usefulness and ease of use. Findings: The developed methodology allows companies to obtain a broader vision of their future prospects. The executives' participation in the process provided them a vision and understanding of the most relevant and sensitive variables of their environment. Research limitations/implications: The proposed methodology is easy to use. It provides a simple and agile mechanism to adapt the strategy of an organization to the changes in the market and environment. Social implications: This process will provide social benefit for the global community, from both a methodological perspective and a practical one, as it will provide a tool that will positively impact competitiveness and quality of life for workers and the wider community. Originality/value: This paper allows the identification of the possible scenarios and their incorporation into a strategy map, which may help companies deal with the changes in their competitive environment. The strategy maps generated for each of the scenarios provide useful information with respect to presented events. Abstract : Propósito: el objetivo de este documento es diseñar un método o proceso que relacione las condiciones ambientales dinámicas con los objetivos estratégicos presentes en el mapa estratégico de la empresa, permitiendo un análisis y la rápida generación de las nuevas estrategias que la empresa pueda adoptar de manera oportuna en para mantener y/o mejorar su posición competitiva en el mercado. Diseño/metodología/enfoque: se realizó una sesión de capacitación y tres talleres en los que participó el personal de la empresa. El equipo de intervención revisó y analizó los resultados logrados y preparó la presentación final. Finalmente, se les pidió a los ejecutivos de las empresas intervenidas que evaluaran la metodología de intervención con respecto a la utilidad y facilidad de uso. Resultados: la metodología desarrollada permite a las empresas obtener una visión más amplia de sus perspectivas futuras. La participación de los ejecutivos en el proceso les proporcionó una visión y comprensión de las variables más relevantes y sensibles de su entorno. Limitaciones/implicaciones de la investigación: la metodología propuesta es fácil de usar. Proporciona un mecanismo simple y ágil para adaptar la estrategia de una organización a los cambios en el mercado y el entorno. Implicaciones sociales: este proceso proporcionará beneficios sociales para toda la comunidad, tanto desde una perspectiva metodológica como práctica, ya que proporcionará una herramienta que tendrá un impacto positivo en la competitividad y la calidad de vida de los trabajadores y la comunidad en general. Originalidad/valor: este documento permite identificar posibles escenarios y su incorporación en un mapa estratégico, lo que puede ayudar a las empresas a lidiar con los cambios en su entorno competitivo. Los mapas estratégicos generados para cada uno de los escenarios brindan información útil con respecto a los eventos presentados.